Factors affecting the calving rate in local breeds of cattle in Zambia - Rakha, A.M.; Igboeli, G. (1970)
The reproductive performance of indigenous cattle in Zambia are examined. Information on general causes of infertility, age of puberty for males and females, oestrus cycle, pregnancy and calving rate of cows, and sperm production of bulls as well as chemical composition of semen are provided.